Interrelationship of awareness, knowledge and readiness of Sarawak civil servants on goods and service tax (GST) / Mohammad Nazri Abdul Rahman - Abdul Rahman, Mohammad Nazri (2015)
Goods and Service Tax (GST) was introduced in France 1950s and has been adopted by more than 120 countries, including all member states of the European Union (EU). Almost all countries that have established the GST system adopt the consumption type GST in which all purchasers of capital goods from other firms are deductible from a firm (Chalet, 2009) However, some countries as Argentina, Peru and Turkey have adopted the income type GST, and countries such as China, Finland, Morocco and Senegal have employed GDP-type GST.